2019
DOI: 10.1097/sla.0000000000003539
|View full text |Cite
|
Sign up to set email alerts
|

Defining Benchmark Outcomes for ALPPS

Abstract: Objective: The aim of this study was to use the concept of benchmarking to establish robust and standardized outcome references after the procedure ALPPS (Associating Liver Partition and Portal Vein Ligation for Staged hepatectomy). Background and Aims: The recently developed ALPPS procedure, aiming at removing primarily unresectable liver tumors, has been criticized for safety issues with high variations in the reported morbidity/mortality rates depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 37 publications
1
78
0
Order By: Relevance
“…Unfortunately, a high 90‐day mortality (12%) was observed following ALPPS, which raised skepticism 5 . Since then, due to better patient selection and the refinement of the surgical technique, morbidity and mortality rates decreased 6,7 . Nevertheless, ALPPS still carries significant risks of mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a high 90‐day mortality (12%) was observed following ALPPS, which raised skepticism 5 . Since then, due to better patient selection and the refinement of the surgical technique, morbidity and mortality rates decreased 6,7 . Nevertheless, ALPPS still carries significant risks of mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…With accumulating experience in some expert centers, ALPPS has been re-considered for non-CRLM tumor entities like neuroendocrine liver metastases [93], intrahepatic CC [94], HCC [95,96], and PHC [97] in selected cases. In an attempt to define reference values for ALPPS, a recent benchmark analysis focusing on a low-risk [43] 2 0 0 4 3 3 1 0 0 3 1 -7 6 5 6 0 Tanaka et al [48] 2 0 0 7 2 2 7 3 5 0 -1 0 0 2 3 0 Wicherts et al [49] 2 0 0 8 5 9 7 8 -1 2 6 6 9 5 9 7 Homayounfar et al [50] population with CRLM found a 90-day mortality rate ≤ 5%, major complications (Clavien-Dindo grade ≥ 3a) ≤65%, postoperative liver failure after stage 2: ≤5%, and completion of stage 2 surgery ≥96% [98]. Of note, in this population, the FLR increased from 0.21% (SD 0.12) to 0.41 (SD 0.09) after a median interstage interval of 13 days [98].…”
Section: Associating Liver Partition With Portal Vein Ligation For Stmentioning
confidence: 99%
“…In an attempt to define reference values for ALPPS, a recent benchmark analysis focusing on a low-risk [43] 2 0 0 4 3 3 1 0 0 3 1 -7 6 5 6 0 Tanaka et al [48] 2 0 0 7 2 2 7 3 5 0 -1 0 0 2 3 0 Wicherts et al [49] 2 0 0 8 5 9 7 8 -1 2 6 6 9 5 9 7 Homayounfar et al [50] population with CRLM found a 90-day mortality rate ≤ 5%, major complications (Clavien-Dindo grade ≥ 3a) ≤65%, postoperative liver failure after stage 2: ≤5%, and completion of stage 2 surgery ≥96% [98]. Of note, in this population, the FLR increased from 0.21% (SD 0.12) to 0.41 (SD 0.09) after a median interstage interval of 13 days [98]. A Scandinavian multicenter RCT comparing ALPPS and TSH in 100 patients confirms the evidence from single, retrospective series and registry data that ALPPS is associated with significantly higher resection rates (ALPPS, 92% vs. TSH, 57%).…”
Section: Associating Liver Partition With Portal Vein Ligation For Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an establishment of clinical databases from international centers with an accurate collection of demographic, management, and outcome data for respective surgical procedures is needed. The importance of establishing benchmarks has been demonstrated for various surgical procedures in general and visceral surgery (11)(12)(13)(14)(15). As yet, there is very little published about acceptable neurosurgical benchmarks.…”
Section: Introductionmentioning
confidence: 99%